Analisis Penggunaan Metode Muroja’ah Berbantu Media Audio Dalam Peningkatan Kualitas Menghafal Al Qur’an Di Smp Al Bayyinah Cisoka Kabupaten Tangerang - Dewi Wulandari (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2024)
Analysis of the Use of the Muroja'ah Method Assisted by Audio Media in Improving the Quality of Memorizing the Qur'an at Al Bayyinah Cisoka Middle School. This research uses qualitative research with data collection methods through observation, interviews, documentation. Data analysis, through data reduction, data presentation, and data verification which ends with checking the validity of the data. The results of this research indicate that the application of the muroja'ah learning model assisted by audio media in Islamic Religious Education Subjects at Al Bayyinah Cisoka Middle School is carried out through four stages 1. Learning approach stage, 2. Methods or strategies used, 3. Learning media, 4 . Learning evaluation system. The implication of this research is that teachers should be able to get used to using audio-assisted learning in the learning process, because it can motivate students in the learning process. The use of varied learning methods must continue to be improved in order to create enjoyable learning for students. By carrying out cycle I, they obtained an average score of 17.63 and experienced an increase in cycle II, they obtained an average score of 18.09 and were included in the complete category.